Representation of women plenary speakers at the American Academy of Neurology Annual Meeting. (1st December 2020) - Singhal, Divya; Bank, Anna M.; Poorman, Julie A.; Doshi, Tina L.; Parekh, Ranna; Parangi, Sareh; Hopf, Harriet W.; Chandrabose, Rekha; Larson, Allison R.; Silver, Julie K.
Abstract : Objective: To determine whether women have been equitably represented among plenary speakers at the American Academy of Neurology (AAN) Annual Meeting by counting and categorizing speakers and comparing outcomes to AAN membership and US neurology workforce data. Methods: Lists of plenary speakers between 1958 and 2019 (62 years) were obtained from the AAN. The primary outcome measures were numbers and proportions of men and women in aggregate and among physicians. Results: We identified 635 plenary speakers, including 148 (23.3%) women. Specifically, women made up 14.6% (19 of 130) of presidential and 25.5% (129 of 505) of nonpresidential plenary session speakers. The inclusion of women plenary speakers was meaningfully higher ( h = 0.33; difference 14.9%; 95% confidence interval 4.2%–26.7%) for nonphysicians (27 of 74 [36.5%]) than physicians (121 of 561 [21.6%]). Although at zero levels for Annual Meetings held between 1958 and 1990 and at mostly low but varying levels thereafter, the representation of women and women physicians has been at or above their proportions in the AAN membership and US neurology workforce since 2017. Comparison of representation by plenary session name revealed an unequal distribution of women, with women physicians concentrated in the Sidney Carter Award in Child Neurology presidential session. Conclusion: Historically and recently, women and women physicians were underrepresented among AAN plenary speakers. As the AAN has taken active steps to address equity, women have been included in more representative proportions overall. However, notable gaps remain, especially in specific prestigious plenary sessions, and further research is needed to determine causality.